Information literacy in Utah: a state of the state. Issue 3 (1st August 2019) - Diekema, Anne R.; Gerrity, Caitlin; Mitchell, Paula
Abstract : Purpose: Ideally, information literacy instruction is sequenced throughout students' academic careers, reinforcing and building on earlier instruction. The purpose of this exploratory study is to identify structural problems that potentially impact student learning. This research surveyed school librarians and academic instruction librarians along the K-20 pipeline to capture information about their instruction programs, their pedagogical approaches and their perceptions on student information literacy skills at points of transition. Design/methodology/approach: The study uses a 58-item survey instrument to capture the perceptions on elements of information literacy instruction from school librarians and academic instruction librarians in the state of Utah. The exploratory survey generated 255 eligible responses. Findings: The study identifies several areas where the information literacy pipeline has challenges: staffing, scheduling, curriculum integration, teacher collaboration and student assessment. Suggestions for improvement include providing educational support for paraprofessionals, facilitating cross-institutional collaboration and creating a scope and sequence document that spans the entire educational spectrum paired with specifically teaching for transfer. Research limitations/implications: The study was limited to surveying the perceptions of library employees who teach students information literacy as part of a school or university. Study findings imply that better support for information literacy learners requires increased collaboration across the pipeline. Originality/value: Information literacy education is often siloed – in the way it is taught, studied and discussed. This research is unique in that it explores the information literacy pipeline as a whole, as each level of instruction is related to the next and studying a single section might obscure larger issues.